Government's subsidisation policy and utilisation of smoking cessation treatments: a population-based cross-sectional study in Taiwan. Issue 1 (13th January 2021) - Wang, Sheng-Kuang; Kao, Chi-Wen; Chuang, Hui-Wan; Tseng, Yi-Kai; Chen, Wan-Chun; Yeh, Chien-Chih; Lai, Chung-Yu; Yen, Li-Chen; Chiu, Yu-Lung
Abstract : Objectives: This study examined the associations between the Second-Generation Cessation Payment Scheme (SCPS) and the use of smoking cessation treatments. Furthermore, these associations were compared between light and heavy smokers in Taiwan. Design: This study had a cross-sectional design. Setting: Data were obtained from the Taiwan Adult Smoking Behaviour Surveillance System 2010–2011 and 2013–2014; data for each year consisted of a nationally representative sample of adults aged 18 years and older. Participants: Current smokers who had either quit or made a serious attempt to quit smoking were selected for the analysis. Primary outcome measure: The primary outcome measure was the use of a smoking cessation clinic or pharmacy in a twice daily to quit smoking. Results: According to multivariate analysis, the SCPS was positively associated with the combined use of a smoking cessation clinic and a pharmacy (OR=3.947; 95% CI: 1.359 to 11.463) when individual-level predictors (gender, age, education level, marital status, monthly household income, daily cigarette consumption, smoking status and self-reported health) were controlled. Heavy smokers showed a signiﬁcant increase in the sole use of a pharmacy (OR=1.676; 95% CI: 1.094 to 2.569) and combined use of a smoking cessation clinic and pharmacy (OR=8.984; 95% CI: 1.914 to 42.173) after the SCPS was introduced. In addition, when related factors were controlled, the use of smoking cessation services was more frequent among heavy smokers than light smokers, including any treatment (OR=1.594; 95% CI: 1.308 to 1.942), a smoking cessation clinic (OR=1.539; 95% CI: 1.232 to 1.922), a pharmacy (OR=1.632; 95% CI: 1.157 to 2.302) and the combination of a smoking cessation clinic and pharmacy (OR=4.608; 95% CI: 1.331 to 15.949) . Conclusions: The SCPS subsidisation policy increased the use of smoking cessation treatments, particularly among heavy smokers.